The Sage handbook of qualitative research - Denzin, Norman K.; Lincoln, Yvonna S. (Sage, 2011)
The editors and contributors address issues of social justice and examine how people's struggles can inform public issues and in turn be transformed into social policy. Their writings are underpinned by a critical framework, and they are committed to addressing issues of inequality. As with previous editions, their aim is to show how the practices of qualitative research can effect change in the world in positive ways.--From publisher description.